2023
DOI: 10.1101/2023.04.10.536216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The soil-borne white root rot pathogenRosellinia necatrixexpresses antimicrobial proteins during host colonization

Abstract: Rosellinia necatrixis a prevalent soil-borne plant-pathogenic fungus that is the causal agent of white root rot disease in a broad range of host plants. The limited availability of genomic resources forR. necatrixhas complicated a thorough understanding of its infection biology. Here, we sequenced nineR. necatrixstrains with Oxford Nanopore sequencing technology, and with DNA proximity ligation we generated a gapless assembly of one of the genomes into ten chromosomes. Whereas many filamentous pathogens displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…While effectors with antimicrobial activity were initially described in the context of plant infection by the pathogenic soil‐borne and broad host‐range pathogen Verticillium dahliae , other fungal pathogens may produce such effectors too. More recently, it was reported that the soil‐borne white root rot pathogen Rosellinia necatrix expresses antimicrobial effector proteins during host colonization, while smut fungi express a conserved extracellular ribonuclease with broad‐spectrum cytotoxic activity to compete with host‐associated bacteria on the leaves of host plants (preprint: Chavarro‐Carrero et al , 2023 ; preprint: Ökmen et al , 2023 ). Pathogenic oomycetes seem to rely on a similar strategy, since Albugo candida secretes antimicrobials into the apoplast of A. thaliana leaves to repress the growth of keystone bacteria (Gómez‐Pérez et al , 2023 ).…”
Section: Intermicrobial Competition Evolved To Protect the Holobiontmentioning
confidence: 99%
“…While effectors with antimicrobial activity were initially described in the context of plant infection by the pathogenic soil‐borne and broad host‐range pathogen Verticillium dahliae , other fungal pathogens may produce such effectors too. More recently, it was reported that the soil‐borne white root rot pathogen Rosellinia necatrix expresses antimicrobial effector proteins during host colonization, while smut fungi express a conserved extracellular ribonuclease with broad‐spectrum cytotoxic activity to compete with host‐associated bacteria on the leaves of host plants (preprint: Chavarro‐Carrero et al , 2023 ; preprint: Ökmen et al , 2023 ). Pathogenic oomycetes seem to rely on a similar strategy, since Albugo candida secretes antimicrobials into the apoplast of A. thaliana leaves to repress the growth of keystone bacteria (Gómez‐Pérez et al , 2023 ).…”
Section: Intermicrobial Competition Evolved To Protect the Holobiontmentioning
confidence: 99%
“…Recently, major efforts were made to develop new functional annotation methods, relying mostly on machine-learning prediction, but these were not aimed to discover antimicrobial activities 5862 . Following the recent characterization of various fungal effectors with antimicrobial activities 5,2833 , we aimed to develop a method to predict antimicrobial activity in fungal secretomes and assist discoveries of such proteins across the fungal tree of life.…”
Section: Discussionmentioning
confidence: 99%
“…The secretomes of plant-associated fungi include diverse carbohydrate-active enzymes (CAZymes) that digest host cell walls, but also small proteins termed “effectors” that promote fungal colonization of plant tissues 2426 . While modulation of host immunity and, in a broader sense, host physiology was long thought to be the main function of effector proteins 26,27 , recent discoveries of antimicrobial activities displayed by effectors of diverse fungi suggest that microbial antagonism may be one of their key roles as well 5,2833 . For instance, the plant-pathogenic fungus Verticillium dahliae secretes antimicrobial proteins during both the soil-dwelling stages of its life cycle and during host colonization, to antagonize niche competitors and foster the invasion of both soil and plant tissues 5,29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together with the intimate association between plants and their microbiota, and the importance of the microbiota for plant health, this broader definition of effectors has led to the hypothesis that pathogens have evolved to target host‐associated microbiota, in addition to the endogenous immune system of the host, using effectors to facilitate disease establishment (Snelders et al ., 2018). Indeed, several fungal pathogens were recently shown to secrete effectors with antimicrobial activities that directly manipulate the microbiota of their hosts (Snelders et al ., 2020, 2021, 2023; Chavarro‐Carrero et al ., 2023; Ökmen et al ., 2023). Whether this also applied to oomycete plant pathogens was unknown until now.…”
Section: Figmentioning
confidence: 99%